Abdurrahman Wahid's View of Pancasila as the State's Basis - Warno Warno (The International Journal of Politics and Sociology Research, 2021)
The development of Islam has indeed become an integral part of Indonesian history. The debate on the relationship between religion and power has become an interesting discourse among religious observers and academics. If religion is treated as a constructive tool, then by itself religion can be used as a means to control all policies carried out by the authorities. Even during the colonial period, religion was used as a means of carrying out the "Ideology of Jihad" to fight the colonial expansion, even though at first it was only socio-cultural in nature. The goal to be achieved from writing this thesis is to find out how the relationship between religion and the state according to Abdurrahman Wahid. Knowing how Abdurrahman Wahid thought about Pancasila as the basis of the Unitary State of the Republic of Indonesia. During the New Order era, Pancasila really has a special place, within the Indonesian nation. In every corner of the country, the name Pancasila always echoes. In schools, in markets, in homes, and especially in government agencies. From big to small, young and old, all must understand Pancasilaism. This was widely advertised in order to create a stigma that the New Order had placed Pancasila as a tool for the political interests of the rulers, to protect the dictatorship's attitude, including "killing" political opponents who were not in line with it.